تقويم أداء مديري مدارس التعليم العام في ضوء مبادئ إدارة الجودة الشاملة "دراسة ميدانية في مدينة اللاذقية" - طيوب, محمود; درويش, رمضان; حسين, محمود حسن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث تقويم أداء مديري المدارس في ضوء مبادئ إدارة الجودة الشاملة, وذلك من خلال الوقوف على واقع عمل المدير الذي يعتبر بمثابة العمود الفقري في عملية التطوير والتحسين المستمر للأداء في الوقت الذي أصبحت فيه هناك حاجة ماسة وملحة للجودة الشاملة في التعليم وإداراتها والرقابة عليها لنهضة التعليم والمجتمع, ولتحقيق أهداف البحث تمّ تصميم استبانة تقويم الأداء تضمنت عمل مدير المدرسة من خلال أربعة مستويات: المستوى الإداري, المستوى الفني, المستوى الاجتماعي, المستوى الإبداعي, وبعد الدراسة والتحليل تمّ التوصل إلى النتائج التالية: -ضعف المستوى الإداري من ناحية عدم وجود معايير واضحة ومحددة في تقييم عمل اللجان المدرسية. - ضعف المستوى الفني من ناحية تحديد احتياجات المدرسة للوسائل التعليمية, والإشراف التربوي والتقويم. - ضعف المستوى الاجتماعي من ناحية ربط المدرسة بالمجتمع المحلي, وتنظيم برامج اجتماعية لتعزيز العلاقة بين المعلمين والطلاب. - ضعف المستوى الإبداعي من ناحية التجديد والابتكار. This research studies evaluation of governmental education schools managers performance within framework of Total quality management principles, by studying real manager work, that it is considered as the strong base in development and continuous process of the performance, and at the same time it is the real need for the total quality in the education and its management and censorship, for raising it and the society. For achieving these goals, we designed a performance evaluation form; it has included the work of manger through, four levels: Managerial level, technical level, social level, creational level. After studying and realizing, we reached to these consequences: - Lack of the managerial level, which means: there are no defined and clear standards in the schooled commission work. - Lack of technical level, which means: defining needs of the school to educational devices, and education supervision, and the evaluation. - Lack of the social level, which means: joining school with local society, and organizing social programs for confirming the relation between teachers and students. - Lack of the creational level, which means: modernizing and creating.